Distribution and Characteristics of Internal Waves Observed During the Expedition of Jalacitra 2-2022 Banda - Putra, I Wayan Sumardana Eka; Atmadipoera, Agus Saleh; Manik, Henry Munandar; Harsono, Gentio; Purwandana, Adi; Hascaryo, Anom Puji (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Indonesian seas have been known as the hotspot for internal waves (IWs) generation sites. The sinking tragedy of the Indonesian Naval Submarine, KRI Nanggala 402 on 21 April 2021 in the northern Bali Sea was highlights the need of detecting, mapping, and characterizing internal waves in Indonesian waters are compulsory mainly in the Indonesian Archipelago Sea Lanes (IASLs). IASLs is a gateway for sea crossings which can be used by civil navigations, intercontinental trade, and foreign military. This study focused on mapping the distribution and characteristics of internal waves qualitatively using EA 600 Single beam Echosounder (SBES) of the Indonesian Naval Vessel, KRI Rigel 933 during The Jala Citra Expedition 2-2022 Banda. The measurements were conducted around the IASLs route in the Bali Waters, Banda Waters and Buru Waters. The results show that the typical high-frequency non-linear internal waves (HFNWs) with an amplitude of less than 10 m were observed intermittently during the expedition, detected mostly in the narrow passages, rough topography and shallowing waters. Typical characteristics of internal solitary waves (ISWs) were also observed with typical amplitudes of ~20 – 65 m. An ISWs extreme events found in this study verified the "turbulent water" that was reported in in the IASLs around the Underwater Seamount (US) Nieuwerkerk waters, in 1925 during the Snellius Expedition. The detection of internal wave events using acoustic equipment, the single beam echosounder is considered effective which can later be used as the guidance for marine activities in the water column.